White Cloth/Shroud as Dowry in Islamic Law - Ashar Ridwan; Susi Susilawati; Marini Citra Dewi; Ahmad Aswar Rowa (Faculty of Law, Universitas Pekalongan, 2023)
This study aims to find out the giving of dowry in the form of a white cloth/shroud in Balaesang Tanjung, Donggala Regency reviewed by Islamic Law. The initial survey was taken through direct information from the Head of the Religious Affairs Office (KUA) in the local sub-district, that the KUA had input data on marriage events as mentioned above. Dowry should be in the form of a materialistic item and can be used by the wife if it is in difficult circumstances. At least, these items can be used for worship as is common, namely a set of prayer tools. Death is a definite thing and not a personal obligation (fardu 'ain) of the wife in its management but is included in the category of fardu kifayah. Although Islam recommends giving the cheapest dowry so as not to be burdensome, dowry in the form of a white cloth/shroud is still very rare. On that basis, how is the review of Islamic Law on the tradition of giving dowry in the form of a white cloth/shroud in Balaesang Tanjung, Donggala regency? The method used is an empirical research method with primary data sources from the community, religious leaders, and community leaders in Balaesang Tanjung, Donggala Regency. The conclusion is that the tradition of dowry of white cloth/shroud in Balaesang Tanjung is in accordance with Islamic teachings, namely including 'urf in the rules of fiqh al-'adatul muhakkamah. Important aspects of dowry in Islam have been included in it such as the existence of women's rights, signs of seriousness in marriage, raising women's dignity, mandatory and should not be eliminated.